Do Ruminal Ciliates Select Their Preys and Prokaryotic Symbionts? - Park, Tansol; Yu, Zhongtang (Frontiers in Microbiology, 2018)
Ruminal ciliates both preys on and form symbiotic relationships with other members of the ruminal microbiota for their survival. However, it remains elusive if they have selectivity over their preys or symbionts. In the present study, we investigated the above selectivity by identifying and comparing the free-living prokaryotes (FLP) and the ciliate-associated prokaryotes (CAP) using Illumina MiSeq sequencing of 16S rRNA gene amplicons. We used single ciliates cells of both monocultures of Entodinium caudatum and Epidinium caudatum and eight different ciliate genera isolated from fresh rumen fluid of dairy cows. Irrespective of the source (laboratory monocultures vs. fresh isolates) of the single ciliate cells, the CAP significantly differed from the FLP in microbiota community profiles. Many bacterial taxa were either enriched or almost exclusively found in the CAP across most of the ciliate genera. A number of bacteria were also found for the first time as ruminal bacteria in the CAP. However, no clear difference was found in methanogens between the CAP and the FLP, which was confirmed using methanogen-specific qPCR. These results suggest that ruminal ciliates probably select their preys and symbionts, the latter of which has rarely been found among the free-living ruminal prokaryotes. The bacteria enriched or exclusively found in the CAP can be target bacteria to detect and localize using specific probes designed from their 16S rRNA sequences, to characterize using single-cell genomics, or to isolate using new media designed based on genomic information.